Um estudo sobre as colaborações interdisciplinares na comunidade científica brasileira - Geraldo José Pessoa Junior (2019)
Interdisciplinary collaborations have recently drawn the attention of scholars, since such relationships contribute to make scientific communities stronger. However, previous studies have focused on characterizing specific groups rather than on studying a complete and robust scientific community. In this MSc dissertation, instead of analyzing particular scenarios, we characterize these collaborations with respect to the eight Brazilian scientific communities defined according to the upper level of the CNPq knowledge area classification scheme. The results show that the Brazilian collaboration network grew and became especially interdisciplinary. In particular, according to our analysis 35.2% of all collaborations in this network are interdisciplinary and 57.6% of the researchers have at least one such scientific interaction. In addition, our study also explores geographical and temporal aspects, thus identifying distinct collaboration patterns involving the aforementioned scientific communities.